BUDAYA DAN BAHASA KELUARGA MULTI-SUKU DI KELURAHAN NARAM KOTA SINGKAWANG - Sheila Aisyah Farenti (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2023)
In Indonesia, there are many tribes including the Malay, Javanese, Batak, Sundanese, Dayak and many more. Each tribe has its own culture and language. Then the culture develops and experiences some renewal in traditions or customs. The Malay tribe and the Javanese tribe really uphold, appreciate and respect existing customs. At present, the Malay and Javanese tribes are still very attached to the customs that have been created since long ago even though there are updates and decreases. The culture or tradition that is still carried out today is Saprahan in the Malay tribe and Kenduri in the Javanese tribe. This research was conducted to find out the culture and language found in multi-tribe families. This research method uses qualitative methods with interview and observation techniques in multi-tribe families to collect research data. So from this research it is known that the culture of the Malay and Javanese tribes is still carried out today and has experienced renewal and decline. From the renewal and decline, there is an influence on both tribes such as the existence of culturation and the replacement of a tradition. For language use, it is influenced by environmental factors. Therefore, it is important to maintain the culture and language that has been produced by the ancestors in order to remain a self-identity.